Conductive composite dispersion, capacitor and conductive laminate

The conductive composite dispersion, comprising a π-conjugated conductive polymer, polyanion, sugar alcohol, guar gum, and water, addresses the challenge of achieving low ESR in capacitors by forming a solid electrolyte layer with improved performance.

JP2025075316APending Publication Date: 2025-05-15SHIN ETSU POLYMER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023186383
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-15

AI Technical Summary

Technical Problem

Capacitors with solid electrolyte layers require a low equivalent series resistance (ESR) to achieve high performance, but existing technologies struggle to achieve this effectively.

Method used

A conductive composite dispersion is developed, containing a π-conjugated conductive polymer, a polyanion, water, a sugar alcohol with 4 to 7 carbon atoms and 3 to 7 hydroxyl groups, and guar gum, with a viscosity of less than 180 mPa·s at 25°C, suitable for forming a solid electrolyte layer with low ESR.

Benefits of technology

The conductive composite dispersion enables the formation of a solid electrolyte layer with excellent performance, reducing the ESR of capacitors and improving their overall performance, while also being suitable for manufacturing conductive laminates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025075316000002
    Figure 2025075316000002
  • Figure 2025075316000001
    Figure 2025075316000001
Patent Text Reader

Abstract

To provide a conductive composite dispersion suitable for the production of a high performance capacitor.SOLUTION: There is provided a conductive composite dispersion which comprises a conductive composite containing a π-conjugated conductive polymer and a polyanion, water, a sugar alcohol having 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the molecule and guar gum and has a viscosity at 25°C of less than 180 mPa s. The content of the guar gum preferably is 0.01 pt.mass or more and less than 2.0 pts.mass based on 100 pts.mass of the total of the conductive composite and the water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive composite dispersion containing a π-conjugated conductive polymer and a polyanion, a capacitor, and a conductive laminate. [Background technology]

[0002] A π-conjugated conductive polymer, the main chain of which is composed of a π-conjugated system, forms a conductive complex by being doped with a polyanion having an anionic group, and becomes dispersible in water. A method for producing a capacitor has been disclosed in which a paint made from a conductive composite dispersion liquid containing a conductive composite is applied to a dielectric layer provided on the surface of an anode made of a valve metal, the paint is dried to form a solid electrolyte layer, and a cathode is placed opposite the solid electrolyte layer (e.g., Patent Document 1). According to this disclosure, the capacitor performance is improved by including a specific unsaturated aliphatic alcohol compound in the paint. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-071400 Summary of the Invention [Problem to be solved by the invention]

[0004] A capacitor with a solid electrolyte layer is required to have a low equivalent series resistance (ESR).

[0005] The present invention provides a conductive composite dispersion suitable for producing high performance capacitors. [Means for solving the problem]

[0006] [1] A conductive complex dispersion comprising: a conductive complex containing a π-conjugated conductive polymer and a polyanion; water; a sugar alcohol having 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the molecule; and guar gum, and having a viscosity of less than 180 mPa s at 25°C. [2] The conductive complex dispersion liquid according to [1], wherein the content of the guar gum is 0.01 parts by mass or more and less than 2.0 parts by mass per 100 parts by mass of the conductive complex and the water combined. [3] The conductive complex dispersion according to [1] or [2], wherein the content of the conductive complex is 0.1 parts by mass or more and less than 3.0 parts by mass per 100 parts by mass of the conductive complex and the water combined. [4] The conductive composite dispersion according to any one of [1] to [3], wherein the content of the water relative to the total mass of the conductive composite dispersion is 70 mass % or more and 99 mass % or less. [5] The conductive complex dispersion liquid according to any one of [1] to [4], wherein the sugar alcohol contains at least one of sorbitol, mannitol, erythritol, and pentaerythritol. [6] The conductive composite dispersion liquid according to any one of [1] to [5], further containing an organic solvent having a boiling point of 150° C. or higher at 1 atmospheric pressure. [7] The conductive composite dispersion according to any one of [1] to [6], further comprising a neutralizing agent. [8] The conductive composite dispersion liquid according to any one of [1] to [7], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid. [9] A capacitor comprising: an anode made of a porous body of a valve metal; a dielectric layer made of an oxide of the valve metal; a cathode made of a conductive material provided on the dielectric layer opposite the anode; and a solid electrolyte layer formed between the dielectric layer and the cathode, wherein the solid electrolyte layer is a cured product of the conductive composite dispersion according to any one of [1] to [8].

[10] A conductive laminate comprising a substrate and a conductive layer formed on at least a portion of a surface of the substrate, the conductive layer being a cured product of the conductive composite dispersion according to any one of [1] to [8]. Effect of the Invention

[0007] Since the conductive composite dispersion of the present invention contains guar gum in a low viscosity range, it can form a solid electrolyte with excellent performance in an anode made of a porous valve metal. This property is suitable not only for the production of capacitors but also for the production of conductive laminates in which a conductive layer is laminated on a substrate.

[0008] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."

[0009] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a cross-sectional view illustrating one embodiment of a capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] <<Conductive composite dispersion>> The conductive composite dispersion according to the first embodiment of the present invention contains a conductive composite including a π-conjugated conductive polymer and a polyanion, water, a specific sugar alcohol, and guar gum, and has a viscosity of less than 180 mPa s at 25° C. Since the viscosity is low, it is easy to impregnate an object to be coated with the conductive composite dispersion, and is suitable for producing a capacitor.

[0012] The viscosity of the conductive composite dispersion of this embodiment at 25°C is preferably lower in the order of 150 mPa·s or less, 120 mPa·s or less, 100 mPa·s or less, 80 mPa·s or less, 60 mPa·s or less, 40 mPa·s or less, 30 mPa·s or less, and 20 mPa·s or less. There is no particular lower limit to the viscosity, but a guideline is, for example, 2 mPa·s. The viscosity was measured at 25° C. using a tuning fork vibration viscometer in accordance with JIS Z8803:2011 (viscosity measurement method using a vibration viscometer).

[0013] <Conductive composite> The conductive complex of this embodiment includes a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and the polyanion has excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive complex has water dispersibility.

[0014] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.

[0015] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.

[0016] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity.

[0017] The weight average molecular weight Mw of the polyanion is not particularly limited and is, for example, preferably from 10,000 to 1,000,000, more preferably from 50,000 to 800,000, and even more preferably from 100,000 to 600,000. When the weight average molecular weight Mw of the polyanion is within the above range, the viscosity of the conductive composite dispersion of this embodiment becomes appropriately low, and a capacitor with a low ESR can be easily produced. The weight average molecular weight Mw of the polyanion is measured by gel filtration chromatography and is the average molecular weight based on mass calculated in terms of pullulan.

[0018] The content of the polyanion contained in the conductive composite dispersion of this embodiment is, for example, preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or greater than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the π-conjugated conductive polymer can be sufficiently contained, so that sufficient conductivity can be ensured.

[0019] The content of the conductive complex in the conductive complex dispersion of this embodiment is preferably 0.1 parts by mass or more and 3.0 parts by mass or less, more preferably 0.5 parts by mass or more and 2.5 parts by mass or less, even more preferably 1.0 parts by mass or more and 2.3 parts by mass or less, and most preferably 1.3 parts by mass or more and 2.0 parts by mass or less, relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) and water. When the content is at least the lower limit of the above range, the conductivity of the cured product of the conductive composite dispersion is further increased. When it is equal to or less than the upper limit of the above range, the viscosity of the conductive complex dispersion can be easily reduced.

[0020] The content of the conductive complex (the total content of the π-conjugated conductive polymer and the polyanion) relative to the total mass of the conductive complex dispersion of this embodiment is, for example, preferably 0.1 mass% or more and 3.0 mass% or less, more preferably 0.5 mass% or more and 2.5 mass% or less, and even more preferably 1.0 mass% or more and 2.0 mass% or less. When the content is at least the lower limit of the above range, the conductivity of the cured product of the conductive composite dispersion is further increased. When it is equal to or less than the upper limit of the above range, the viscosity of the conductive complex dispersion can be easily reduced.

[0021] <Sugar alcohol> The conductive composite dispersion of this embodiment contains a specific sugar alcohol. By including the specific sugar alcohol, the conductivity after curing is improved, and the capacitor performance can be improved (capacitance, ESR, and withstand voltage are improved).

[0022] From the viewpoint of fully obtaining the above-mentioned effects, the sugar alcohol preferably has 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the sugar alcohol molecule, more preferably has a non-cyclic structure, and further preferably is one or more selected from pentaerythritol, sorbitol, mannitol, and erythritol.

[0023] The content of the sugar alcohol in the conductive complex dispersion liquid of this embodiment is preferably 1 part by mass or more and 30 parts by mass or less, more preferably 3 parts by mass or more and 20 parts by mass or less, even more preferably 5 parts by mass or more and 15 parts by mass or less, and most preferably 8 parts by mass or more and 12 parts by mass or less, relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) and water. When the content is equal to or greater than the lower limit of the above range, the conductivity and the like of the solid electrolyte layer are increased, so that the ESR of the capacitor can be further reduced. When the content is equal to or less than the upper limit of the above range, the viscosity of the conductive composite dispersion can be kept low, which facilitates penetration into the porous structure of the anode, thereby enabling the ESR of the capacitor to be further reduced.

[0024] The content of the sugar alcohol relative to the total mass of the conductive composite dispersion of this embodiment is, for example, preferably 0.1 mass% or more and 20 mass% or less, more preferably 1.0 mass% or more and 15.0 mass% or less, even more preferably 3.0 mass% or more and 12.0 mass% or less, and most preferably 6.0 mass% or more and 10.0 mass% or less. When the content is equal to or greater than the lower limit of the above range, the conductivity and the like of the solid electrolyte layer are increased, so that the ESR of the capacitor can be further reduced. When the content is equal to or less than the upper limit of the above range, the viscosity of the conductive composite dispersion can be kept low, which facilitates penetration into the porous structure of the anode, thereby enabling the ESR of the capacitor to be further reduced.

[0025] <Guar gum> Guar gum is a water-soluble natural polysaccharide with a main chain of mannose and side chains of galactose, and usually has a molecular weight of 200,000 to 300,000. By containing guar gum within a range that maintains a predetermined low viscosity, the conductive composite dispersion of this embodiment becomes suitable for producing a capacitor with a reduced ESR.

[0026] The content of guar gum in the conductive complex dispersion liquid of this embodiment is preferably 0.01 parts by mass or more and less than 2.00 parts by mass, more preferably 0.01 parts by mass or more and 1.40 parts by mass or less, even more preferably 0.01 parts by mass or more and 0.80 parts by mass or less, particularly preferably 0.01 parts by mass or more and 0.40 parts by mass or less, and most preferably 0.01 parts by mass or more and 0.20 parts by mass or less, relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) and water. When the content is equal to or greater than the lower limit of the above range, the conductivity and the like of the solid electrolyte layer are increased, so that the ESR of the capacitor can be further reduced. When the content is equal to or less than the upper limit of the above range, the viscosity of the conductive composite dispersion can be kept low, which facilitates penetration into the porous structure of the anode, thereby enabling the ESR of the capacitor to be further reduced.

[0027] The content of guar gum relative to the total mass of the conductive composite dispersion of this embodiment is, for example, preferably 0.001 mass% or more and 1.5 mass% or less, more preferably 0.002 mass% or more and 1.0 mass% or less, even more preferably 0.003 mass% or more and 0.50 mass% or less, particularly preferably 0.004 mass% or more and 0.20 mass% or less, and most preferably 0.005 mass% or more and 0.10 mass% or less. When the content is equal to or greater than the lower limit of the above range, the conductivity and the like of the solid electrolyte layer are increased, so that the ESR of the capacitor can be further reduced. When the content is equal to or less than the upper limit of the above range, the viscosity of the conductive composite dispersion can be kept low, which facilitates penetration into the porous structure of the anode, thereby enabling the ESR of the capacitor to be further reduced.

[0028] <Dispersion medium> The dispersion medium contained in the conductive composite dispersion liquid is preferably an aqueous dispersion medium containing water because the conductive composite is hydrophilic. Also, a dispersion medium other than water may be contained. The dispersion medium other than water is not particularly limited as long as it does not significantly impair the dispersibility of the conductive composite. Since the conductive complex has excess anion groups derived from polyanions and has high dispersibility in water, the dispersion medium other than water is preferably a water-soluble organic solvent. Here, the water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and examples of such organic solvents include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvent contained as the dispersion medium may be one type or two or more types. Note that the non-water-soluble organic solvent is an organic solvent that dissolves in an amount of less than 1 g.

[0029] The content of water relative to the total mass of the conductive complex dispersion is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more. Also, it is preferably 99% by mass or less. When the conductive complex dispersion contains water in an amount equal to or more than the above lower limit, the dispersibility of the conductive complex contained in the conductive complex dispersion is increased, and the performance of a capacitor having a solid electrolyte layer formed from the conductive complex dispersion can be further improved. Also, the conductivity of the conductive layer formed from the conductive complex dispersion can be further improved.

[0030] <Neutralizing agent> The conductive complex dispersion of this embodiment may further contain one or more neutralizing agents. When the polyanion has an acid group, the conductive complex dispersion tends to become strongly acidic, but this can be neutralized by a neutralizing agent. Examples of the neutralizing agent include basic compounds. The basic compound functions as a Bronsted base that accepts protons from the excess anion groups of the polyanion. In order to fulfill this function, the amount of the basic compound dissolved in water is preferably 0.001 g or more per 100 g of water at 20° C. The upper limit of the amount dissolved is not particularly limited, but even if it is about 0.1 g, the above function can be fulfilled sufficiently.

[0031] Examples of the basic compound that can be used include organic or inorganic basic compounds containing nitrogen, hydroxides of alkali metals or Group 2 metals, various carbonates and hydrogen carbonates, etc. Examples include hydroxides of alkali metals, quaternary ammonium hydroxides or salts thereof, ammonia, amines, etc. Specific examples of the alkali metal hydroxide include potassium hydroxide and sodium hydroxide. Specific examples of carbonates or hydrogen carbonates include ammonium hydrogen carbonate, ammonium carbonate, potassium hydrogen carbonate, potassium carbonate, sodium hydrogen carbonate, and sodium carbonate. Specific examples of the quaternary ammonium hydroxide or a salt thereof include tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide.

[0032] Examples of the amine include aliphatic tertiary amines and nitrogen-containing aromatic compounds. Examples of the aliphatic tertiary amine include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine.

[0033] Examples of nitrogen-containing aromatic compounds (aromatic compounds in which at least one nitrogen atom forms a ring structure) include pyrrole, indole, imidazole, 2-methylimidazole, 2-propylimidazole, N-methylimidazole, N-propylimidazole, N-butylimidazole, 1-(2-hydroxyethyl)imidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole. Examples of the aryloxy group include 2-phenyl-4,5-dihydroxymethylimidazole, 1-acetylimidazole, 2-aminobenzimidazole, 2-amino-1-methylbenzimidazole, 2-hydroxybenzimidazole, 2-(2-pyridyl)benzimidazole, pyridine, pyrimidine, pyrazine, and derivatives thereof such as alkyl-substituted products (e.g., substituted with an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, propyl, or butyl), halogen-substituted products (e.g., substituted with a halogen group, such as fluoro, chloro, or bromine), and nitrile-substituted products. Of these, nitrogen-containing aromatic compounds are preferred, and imidazole is more preferred.

[0034] The content of the basic compound contained in the conductive complex dispersion liquid is, for example, preferably 1 part by mass or more and 100 parts by mass or less, more preferably 5 parts by mass or more and 60 parts by mass or less, and even more preferably 10 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the conductive complex (total of the π-conjugated conductive polymer and the polyanion). When it is in the above suitable range, the acidity of the conductive complex dispersion liquid is weakened, the corrosiveness to the substrate is reduced, and the ESR of the capacitor can be further reduced.

[0035] The content of the basic compound contained in the conductive composite dispersion is preferably such that the pH of the conductive composite dispersion (25°C) is 2.0 to 8.0, more preferably 2.0 to 5.0, and even more preferably 2.0 to 3.0. Within the above preferred range, the ESR of the capacitor can be further reduced.

[0036] <High boiling point solvent> The conductive composite dispersion of this embodiment may further contain one or more organic solvents (high boiling point solvents) having a boiling point of 150° C. or higher at 1 atmosphere (101,325 Pascals). The boiling point is preferably 250° C. or lower. By including a high boiling point solvent, the effect of improving the conductivity of the cured product of the conductive composite dispersion can be obtained.

[0037] Examples of high boiling point solvents include water-soluble organic solvents and water-insoluble organic solvents, the definitions of which are the same as those described above.

[0038] Examples of the high-boiling water-soluble organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, nitrogen atom-containing solvents, and sulfur atom-containing solvents. Examples of alcohol-based solvents include polyhydric alcohols such as ethylene glycol (boiling point 198°C), 1,2-propanediol (also known as propylene glycol, boiling point 188°C), 1,3-propanediol (boiling point 214°C), 1,2-butanediol (boiling point 194°C), 1,3-butanediol (boiling point 207°C), 1,4-butanediol (boiling point 228°C), dipropylene glycol (boiling point 232°C, mixture of isomers), and diethylene glycol (boiling point 245°C). Examples of ether solvents include diethylene glycol dimethyl ether (boiling point 162° C.) and diethylene glycol diethyl ether (boiling point 188° C.). Examples of ketone solvents include methyl amyl ketone (boiling point 151° C.) and diacetone alcohol (boiling point 168° C.). Examples of nitrogen atom-containing solvents include N-methylpyrrolidone (boiling point 202° C.), N-methylacetamide (boiling point 206° C.), dimethylacetamide (boiling point 165° C.), and N,N-dimethylformamide (boiling point 153° C.). An example of the sulfur atom-containing solvent is dimethyl sulfoxide (boiling point: 189° C.).

[0039] Examples of the high-boiling point water-insoluble organic solvent include hydrocarbon solvents, etc. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include nonane (boiling point 151° C.), decane (boiling point 174° C.), and dodecane (boiling point 216° C.). Examples of aromatic hydrocarbon solvents include propylbenzene (boiling point 159° C.) and isopropylbenzene (boiling point 152° C.).

[0040] Among the above examples, alcohol-based high boiling point solvents are preferred because they provide a greater effect of improving electrical conductivity. Among the alcohol-based high-boiling point solvents, ethylene glycol (boiling point 198°C), 1,2-propanediol (boiling point 188°C), 1,3-propanediol (boiling point 214°C), diethylene glycol (boiling point 245°C), and dimethyl sulfoxide (boiling point 189°C) are preferred because of their excellent effects in improving conductivity, etc.

[0041] The content of the high-boiling point solvent contained in the conductive composite dispersion liquid is, for example, preferably 10 parts by mass or more and 2000 parts by mass or less, more preferably 100 parts by mass or more and 1000 parts by mass or less, and even more preferably 400 parts by mass or more and 800 parts by mass or less, relative to 100 parts by mass of the conductive composite (the total of the π-conjugated conductive polymer and the polyanion). Within the above range, the ESR of a capacitor having a solid electrolyte layer formed from the conductive composite dispersion can be further reduced, and the conductivity of the conductive layer formed from the conductive composite dispersion can be further increased.

[0042] The content of the high-boiling point solvent relative to the total mass of the conductive polymer-containing liquid of this embodiment is, for example, preferably 0.1 mass% or more and 20 mass% or less, more preferably 1.0 mass% or more and 18.0 mass% or less, even more preferably 3.0 mass% or more and 15.0 mass% or less, and most preferably 6.0 mass% or more and 12.0 mass% or less. When it is at least the lower limit of the above range, the ESR and electrical conductivity can be further improved. When it is equal to or less than the upper limit of the above range, an increase in the viscosity of the conductive complex dispersion can be suppressed.

[0043] <Optional Additives> The conductive composite dispersion may contain other optional additives. The content ratio is appropriately determined depending on the type of additive, but can be, for example, 1 to 1000 parts by mass with respect to 100 parts by mass of the total of the π-conjugated conductive polymer and the polyanion. Here, the optional additives are compounds other than the basic compound, the high boiling point solvent, the sugar alcohol, the guar gum, and the dispersion medium.

[0044] Examples of the optional additives include a surfactant, an inorganic conductive agent, an antifoaming agent, a coupling agent, an antioxidant, and an ultraviolet absorbing agent. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinyl alcohol may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group, an amino group, an epoxy group, or the like. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.

[0045] <Method for producing conductive composite dispersion> As a method for producing the conductive composite dispersion of the first aspect of the present invention, for example, a method of adding a sugar alcohol, guar gum, and, if necessary, a neutralizing agent and a high boiling point solvent to an aqueous dispersion of the conductive composite can be mentioned. The blending of each component can be as desired, and it is preferable to blend them so as to be within the above-mentioned preferred range. The aqueous dispersion of the conductive complex may be obtained by chemically oxidizing and polymerizing a monomer that forms a π-conjugated conductive polymer in an aqueous solution of a polyanion by a known method, or a commercially available product may be used.

[0046] <Capacitor manufacturing method> A capacitor can be manufactured by a manufacturing method including a step of applying the conductive composite dispersion of the first embodiment to the surface of a dielectric layer formed on the surface of an anode made of a porous valve metal, and drying the applied conductive composite dispersion to form a solid electrolyte layer.

[0047] The method for manufacturing a capacitor preferably includes a step of oxidizing the surface of an anode made of a porous valve metal to form a dielectric layer (dielectric forming step), a step of arranging a cathode in a position facing the dielectric layer (cathode forming step), and a step of forming a solid electrolyte layer on at least a part of the surface of the dielectric layer (film forming step). Each step will be described below with reference to FIG.

[0048] [Dielectric formation process] In this step, the surface of anode 11 made of a porous valve metal is oxidized to form dielectric layer 12. The method for forming dielectric layer 12 is not particularly limited, and examples thereof include a method in which the surface of anode 11 is anodized in an electrolyte for chemical conversion treatment, such as an aqueous solution of ammonium adipate, an aqueous solution of ammonium borate, or an aqueous solution of ammonium phosphate.

[0049] [Cathode formation process] In this step, the cathode 13 is disposed at a position facing the dielectric layer 12. The method for disposing the cathode 13 is not particularly limited, and examples thereof include a method of forming the cathode 13 using a conductive paste such as a carbon paste or a silver paste, and a method of disposing a metal foil such as an aluminum foil facing the dielectric layer 12.

[0050] [Film forming process] In this step, the conductive composite dispersion liquid is applied to at least a portion of the surface of the dielectric layer 12, and then dried to form the solid electrolyte layer 14.

[0051] Examples of the method for applying the conductive complex dispersion include immersion (dip coating), comma coating, reverse coating, lip coating, and microgravure coating. Among these, a method in which the anode 11 is immersed in the conductive complex dispersion under reduced pressure is preferred. The immersion method allows the conductive complex dispersion to be sufficiently applied even to the inside of the porous structure on the surface of the dielectric layer 12. After immersion, the anode is taken out and subjected to the next drying treatment.

[0052] Examples of the drying method include room temperature drying, hot air drying, far infrared drying, etc. Among these, hot air drying is preferred. The drying temperature is, for example, preferably 100 to 180° C., and more preferably 120 to 150° C. The drying time is, for example, preferably 0.2 to 1 hour. After drying, the capacitor can be assembled in the usual manner.

[0053] The composition of the components contained in the solid electrolyte layer 14 reflects the composition of the applied conductive composite dispersion liquid. The content of the sugar alcohol relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the solid electrolyte layer 14 is, for example, preferably 50 parts by mass or more and 1500 parts by mass or less, more preferably 100 parts by mass or more and 1200 parts by mass or less, even more preferably 200 parts by mass or more and 900 parts by mass or less, and most preferably 300 parts by mass or more and 700 parts by mass or less. When the content is equal to or greater than the lower limit of the above range, the ESR of the capacitor can be further improved. When the content is equal to or less than the upper limit of the above range, a decrease in the ESR of the capacitor can be suppressed.

[0054] The content of the guar gum relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the solid electrolyte layer 14 is, for example, preferably 0.10 parts by mass or more and 100 parts by mass or less, more preferably 0.10 parts by mass or more and 20 parts by mass or less, even more preferably 0.10 parts by mass or more and 10 parts by mass or less, and most preferably 0.10 parts by mass or more and 5.0 parts by mass or less. When the content is equal to or greater than the lower limit of the above range, the ESR of the capacitor can be further improved. When the content is equal to or less than the upper limit of the above range, a decrease in the ESR of the capacitor can be suppressed.

[0055] <Capacitor> The capacitor comprises an anode made of a porous body of a valve metal, a dielectric layer made of an oxide of the valve metal, a cathode made of a conductive material provided on the dielectric layer opposite the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, and the solid electrolyte layer contains a cured product of the conductive composite dispersion of the first aspect.

[0056] An example of an embodiment of the capacitor will be described with reference to Fig. 1. A capacitor 10 shown in Fig. 1 includes an anode 11 made of a porous body of a valve metal, a dielectric layer 12 made of an oxide of the valve metal, a solid electrolyte layer 14 formed on the surface of the dielectric layer 12, and a cathode 13 provided on the outermost side. The cathode 13 is provided on the opposite side to the anode 11, with the dielectric layer 12 and the solid electrolyte layer 14 sandwiched therebetween.

[0057] Examples of valve metals constituting the anode 11 include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. Among these, aluminum, tantalum, and niobium are preferable. Specific examples of the anode 11 include an aluminum foil that has been etched to increase its surface area and then oxidized, and a tantalum or niobium particle sintered body that has been oxidized and pelletized. Such a processed body is a porous body with irregularities on the surface.

[0058] The dielectric layer 12 in this embodiment is a layer formed by oxidizing the surface of the anode 11, for example, by anodizing the surface of the metallic anode 11 in an electrolyte such as an aqueous solution of ammonium adipate. Similar to the anode 11, the dielectric layer 12 also has projections and recesses.

[0059] The cathode 13 in this embodiment may be a conductive layer formed from a conductive paste or a metal layer made of a conductive material such as aluminum foil.

[0060] The solid electrolyte layer 14 in this embodiment is formed on the surface of the dielectric layer 12. The solid electrolyte layer 14 covers at least a portion of the surface of the dielectric layer 12, and may cover the entire surface of the dielectric layer 12. The thickness of the solid electrolyte layer 14 may be constant or may not be constant, and may be, for example, between 1 μm and 100 μm.

[0061] [Electrolyte] The capacitor may have an electrolyte impregnating a solid electrolyte layer. Examples of the solvent constituting the electrolytic solution include alcohol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, and glycerin; lactone-based solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; sulfur-based solvents such as sulfolane, dimethyl sulfoxide, and dimethyl sulfone; amide-based solvents such as N-methylformamide, N,N-dimethylformamide, N-methylacetamide, and N-methylpyrrolidinone; nitrile-based solvents such as acetonitrile and 3-methoxypropionitrile; and water. Examples of the electrolyte constituting the electrolytic solution include organic acids such as adipic acid, glutaric acid, succinic acid, benzoic acid, isophthalic acid, phthalic acid, terephthalic acid, maleic acid, toluic acid, enanthic acid, malonic acid, formic acid, decanedicarboxylic acids such as 1,6-decanedicarboxylic acid and 5,6-decanedicarboxylic acid, octanedicarboxylic acids such as 1,7-octanedicarboxylic acid, azelaic acid, and sebacic acid; or boric acid, a polyhydric alcohol complex compound of boric acid obtained from boric acid and a polyhydric alcohol; inorganic acids such as phosphoric acid, carbonic acid, and silicic acid as anion components, and primary amines (methylamine, ethylamine, propylamine, butylamine, ethylenediamine, etc.), secondary amines (dimethylamine, diethylamine, dipropylamine, methylethylamine, diphenylamine, etc.), tertiary amines (trimethylamine, triethylamine, tripropylamine, triphenylamine, 1,8-diazabicyclo(5,4,0)-undecene-7, etc.), tetraalkylammonium (tetramethylammonium, tetraethylammonium, tetrapropylammonium, tetrabutylammonium, methyltriethylammonium, dimethyldiethylammonium, etc.), etc., as a cationic component.

[0062] The capacitor is not limited to the above configuration, and may have a separator provided between the dielectric layer and the cathode. An example of a capacitor having a separator provided between the dielectric layer and the cathode is a wound type capacitor. Examples of the separator include sheets (including nonwoven fabrics) made of cellulose, polyvinyl alcohol, polyester, polyethylene, polystyrene, polypropylene, polyimide, polyamide, polyvinylidene fluoride, etc., and nonwoven fabrics of glass fibers. The density of the separator is, for example, 0.1 g / cm 3 More than 1.0g / cm 3 The following are included: When a separator is provided, a method of forming a cathode by impregnating the separator with carbon paste or silver paste can also be applied.

[0063] <Method for manufacturing conductive laminate> The conductive laminate can be produced by a production method including a step of applying the conductive composite dispersion according to the first aspect of the present invention to at least a partial surface of a substrate to form a conductive layer.

[0064] Examples of a method for applying (coating) the conductive composite dispersion onto any surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.

[0065] The amount of the conductive composite dispersion applied to the substrate is not particularly limited, but may be, for example, 0.01 to 10.0 g / m as a non-volatile component. 2 The range is preferably:

[0066] The coating film made of the conductive complex dispersion applied onto the substrate is dried to remove at least a portion of the dispersion medium, and then cured to form a conductive layer. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 200° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes.

[0067] <Conductive laminate> The conductive laminate comprises a substrate and a conductive layer formed on at least a portion of the surface of the substrate, and the conductive layer contains a cured product of the conductive composite dispersion of the first aspect.

[0068] [Conductive layer] The conductive layer may be formed over the entire surface of any surface of the substrate, or over a portion of the entire surface. In the conductive film, it is preferable that a conductive layer of substantially uniform thickness is formed over substantially the entire surface of one surface or the other surface of the film substrate. When a conductive layer is formed only over a portion of the surface of the substrate, the conductive layer may be, for example, a fine conductive pattern such as a circuit or an electrode, or the conductive layer may be provided on the same surface and the conductive layer may be not provided on the same surface and may be roughly divided.

[0069] The average thickness of the conductive layer is, for example, preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 50 μm or less, and even more preferably 30 nm or more and 30 μm or less. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.

[0070] The composition of the components contained in the conductive layer reflects the composition of the conductive composite dispersion that is applied. The content of the sugar alcohol relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the conductive layer is, for example, preferably 50 parts by mass or more and 1500 parts by mass or less, more preferably 100 parts by mass or more and 1200 parts by mass or less, even more preferably 200 parts by mass or more and 900 parts by mass or less, and most preferably 300 parts by mass or more and 700 parts by mass or less. When it is in the above range, the conductivity of the conductive layer is good.

[0071] The content of the guar gum relative to 100 parts by mass of the conductive complex (the total of the π-conjugated conductive polymer and the polyanion) contained in the conductive layer is, for example, preferably 0.10 parts by mass or more and 100 parts by mass or less, more preferably 0.10 parts by mass or more and 20 parts by mass or less, even more preferably 0.10 parts by mass or more and 10 parts by mass or less, and most preferably 0.10 parts by mass or more and 5.0 parts by mass or less. When it is in the above range, the conductivity of the conductive layer is good.

[0072] [Base material] The substrate may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface, such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.

[0073] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, and cellulose acetate propionate. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably a polyester resin, and among these, polyethylene terephthalate is preferable.

[0074] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesion of the conductive layer.

[0075] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.

[0076] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.

[0077] The average thickness of the glass substrate is preferably from 100 μm to 3000 μm, more preferably from 100 μm to 1000 μm. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to break, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to a thinner conductive laminate. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values. EXAMPLES

[0078] (Production Example 1) Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid (PSS).

[0079] (Production Example 2) Production of PEDOT-PSS aqueous dispersion 14.2 g of 3,4-ethylenedioxythiophene and a solution in which 36.7 g of polystyrene sulfonic acid was dissolved in 2000 ml of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and while stirring, 29.64 g of ammonium persulfate and 8.0 g of an oxidation catalyst solution of ferric sulfate dissolved in 200 ml of ion-exchanged water were slowly added, followed by stirring for 3 hours to carry out the reaction. To the reaction solution, 2000 ml of ion-exchanged water was added, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated three times. Then, 200 ml of sulfuric acid diluted to 10% by mass and 2000 ml of ion-exchanged water were added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. 2000 ml of ion-exchanged water was added to the remaining liquid, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated three times. Further, 2000 ml of ion-exchanged water was added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated five times to obtain a 1.2 mass% polystyrenesulfonic acid-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS aqueous dispersion) solution. Further ultrafiltration was performed to obtain a 1.6 mass% PEDOT-PSS aqueous dispersion (conductive polymer dispersion A).

[0080] (Production Example 3) A 1.2% by mass solution of polystyrenesulfonic acid-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS aqueous dispersion) was obtained in the same manner as in Production Example 2. Then, ultrafiltration was further performed to obtain a 2.0% by mass aqueous dispersion of PEDOT-PSS (conductive polymer dispersion B).

[0081] (Production Example 4) Preparation of Capacitor Element After connecting an anode lead terminal to the etched aluminum foil (anode foil), a voltage of 40 V was applied in a 10% by mass aqueous solution of ammonium adipate to perform chemical conversion (oxidation treatment) and form dielectric layers on both sides of the aluminum foil to obtain an anode foil. Next, opposing aluminum cathode foils to which cathode lead terminals were welded were laminated on both sides of the anode foil via a cellulose separator, and the resultant was rolled up into a cylindrical shape to obtain a capacitor element.

[0082] (Production Example 5) 77 g of ethylene glycol, 23 g of polyethylene glycol #300, and 1 g of p-hydroxybenzoic acid were mixed together to obtain a driving electrolyte.

[0083] Example 1 To 100 g of the PEDOT-PSS aqueous dispersion obtained in Production Example 2, 0.35 g of imidazole, 10 g of diethylene glycol, 10 g of sorbitol, and 0.05 g of guar gum were added and stirred for 30 minutes to obtain a conductive composite dispersion (hereinafter referred to as a coating composition). The coating composition had a pH of 2.5 and a viscosity as shown in Table 1. Next, the capacitor element obtained in Production Example 4 was immersed in a coating composition under reduced pressure, and then dried at 125°C / 30 minutes in a hot air dryer to form a solid electrolyte layer containing a conductive composite on the surface of the dielectric layer, thereby obtaining a capacitor element. Finally, the capacitor element having the above-mentioned solid electrolyte layer formed thereon and the driving electrolyte solution obtained in Production Example 5 were loaded into an aluminum case, and the case was sealed with a sealing rubber, followed by treatment at 125°C for 30 minutes with an applied voltage of 40 V to produce a capacitor.

[0084] Example 2 To 100 g of the PEDOT-PSS aqueous dispersion obtained in Production Example 3, 0.40 g of imidazole, 10 g of diethylene glycol, 10 g of sorbitol, and 0.01 g of guar gum were added and stirred for 30 minutes to obtain a coating composition. The coating composition had a pH of 2.5 and a viscosity as shown in Table 1. Using the obtained coating composition, a capacitor was produced in the same manner as in Example 1.

[0085] Example 3 A capacitor was produced in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 0.05 g.

[0086] Example 4 A capacitor was prepared in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 0.10 g.

[0087] Example 5 A capacitor was produced in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 0.30 g.

[0088] Example 6 A capacitor was prepared in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 0.50 g.

[0089] Example 7 A capacitor was produced in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 1.0 g.

[0090] Example 8 A capacitor was prepared in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 1.5 g.

[0091] Example 9 A capacitor was prepared in the same manner as in Example 5, except that sorbitol was changed to mannitol.

[0092] Example 10 A capacitor was produced in the same manner as in Example 5, except that sorbitol was changed to erythritol.

[0093] Example 11 A capacitor was produced in the same manner as in Example 5, except that 10 g of sorbitol was changed to 5 g of pentaerythritol.

[0094] Comparative Example 1 A capacitor was prepared in the same manner as in Example 2, except that guar gum was not added.

[0095] Comparative Example 2 A capacitor was produced in the same manner as in Example 5, except that 10 g of sorbitol was replaced with 10 g of ion-exchanged water.

[0096] Comparative Example 3 A capacitor was prepared in the same manner as in Example 2, except that the amount of guar gum was changed from 0.01 g to 2.0 g.

[0097] [pH measurement] The pH was measured at 25°C by a conventional method using a commercially available pH meter.

[0098] [Measurement of capacitance and equivalent series resistance] The capacitance (unit: μF) at 120 Hz and the equivalent series resistance (ESR) (unit: mΩ) at 100 kHz of the capacitors prepared using the conductive composite dispersions of each example were measured using an LCR meter ZM2376 (NF Corporation). The ESR measurement results are shown in Table 1.

[0099] [Method of measuring viscosity] The conductive composite dispersion (paint composition) prepared in each example was used as a sample and measured at 25°C using a tuning fork vibration viscometer (model number: SV-10, manufactured by A&D Corporation) in accordance with JIS Z8803:2011 (Viscosity measurement method using a vibration viscometer). 1 Pa s (Pascal second) was calculated as 1000 cP (centipoise).

[0100] [Table 1]

[0101] From the above, it can be seen that the conductive composite dispersion liquid prepared in the examples according to the present invention contains a small amount of guar gum and sugar alcohol and has a low viscosity, so that the performance of the prepared capacitor is excellent. A comparison of Example 5 with Examples 9 to 11 revealed that, among sugar alcohols, sorbitol is preferable. On the other hand, the conductive complex dispersion of Comparative Example 1 does not contain guar gum, and therefore has an inferior ESR compared to Example 2 which contains the same amounts of sugar alcohol and PEDOT-PSS. The conductive complex dispersion of Comparative Example 2 does not contain sugar alcohol, and therefore has a significantly inferior ESR compared to Example 5 which contains the same amounts of guar gum and PEDOT-PSS. The conductive composite dispersion of Comparative Example 3 contains a large amount of guar gum and has a high viscosity, and therefore has a poorer ESR than Example 2, which contains the same amount of sugar alcohol and PEDOT-PSS. This is thought to be because the conductive composite dispersion, which has a high viscosity, is difficult to penetrate into the porous body of the anode made of valve metal. [Explanation of symbols]

[0102] 10 Capacitor 11 Anode 12 Dielectric layer 13 Cathode 14 Solid electrolyte layer

Claims

1. A conductive complex containing a π-conjugated conductive polymer and a polyanion, water, a sugar alcohol having 4 to 7 carbon atoms and 3 to 7 hydroxyl groups in the molecule, and guar gum, A conductive composite dispersion having a viscosity at 25° C. of less than 180 mPa·s.

2. The conductive complex dispersion according to claim 1 , wherein the content of the guar gum is 0.01 parts by mass or more and less than 2.0 parts by mass with respect to a total of 100 parts by mass of the conductive complex and the water.

3. The conductive complex dispersion according to claim 2 , wherein the content of the conductive complex is 0.1 parts by mass or more and less than 3.0 parts by mass with respect to 100 parts by mass in total of the conductive complex and the water.

4. The conductive complex dispersion according to claim 3 , wherein a content of the water relative to a total mass of the conductive complex dispersion is 70 mass % or more and 99 mass % or less.

5. The conductive complex dispersion according to claim 4 , wherein the sugar alcohol comprises at least one of sorbitol, mannitol, erythritol, and pentaerythritol.

6. The conductive composite dispersion according to claim 5 , further comprising an organic solvent having a boiling point of 150° C. or higher at 1 atmospheric pressure.

7. The conductive composite dispersion of claim 6 further comprising a neutralizing agent.

8. The π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid, or 8. The conductive composite dispersion according to claim 7, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) and the polyanion is polystyrenesulfonic acid.

9. The present invention relates to a valve metal porous body, and a cathode made of a conductive material and provided on the dielectric layer opposite to the anode. A capacitor, wherein the solid electrolyte layer is a cured product of the conductive composite dispersion according to any one of claims 1 to 8.

10. A substrate and a conductive layer formed on at least a portion of the surface of the substrate, A conductive laminate, wherein the conductive layer is a cured product of the conductive composite dispersion according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Conductive polymeric composition, conductive polymeric material, conductive substrate, electrode and solid electrolytic capacitor

    JP2013122015A

  • Capacitor and method of manufacturing the same

    JP2014067949A

  • Conductive polymer aqueous solution and conductive polymer film

    JP2015147834A

  • Conductive polymer composition and conductive polymer film

    JP2023108905A

  • Conductive coating composition and coated member

    WO2011024830A1